2001
DOI: 10.1099/00221287-147-6-1451
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lipopolysaccharide O antigen synthesis genes required for attachment of the S-layer of Caulobacter crescentus The GenBank accession number for the NA1000 rsaADEF and gmd, per, wbqA, wbqR, wbqX and wbqZ sequences reported in this paper is AF06235.

Abstract: The outer surface of Caulobacter crescentus consists of a two-dimensional crystalline protein lattice layer (S-layer). A fraction of the LPS has an O antigen polymer attached to the core to form a ' smooth ' LPS (S-LPS), which is required for attachment of the protein S-layer to the outer-membrane surface. A method to screen for strains defective in LPS production, based on loss of S-layer attachment, was developed and applied to libraries of transposongenerated mutants. Eighteen distinct insertions were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…The x axis of the HPLC spectrum is the elution time (in minutes); the y axis is the absorbance. unable to anchor the exported protein to its lipopolysaccharide layer (43,52). Electron microscopy images also showed that the peptidoglycan layer of the ⌬sll1213 strain was less electron dense than in the ⌬sll1951 strain or the Synechocystis wild type (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The x axis of the HPLC spectrum is the elution time (in minutes); the y axis is the absorbance. unable to anchor the exported protein to its lipopolysaccharide layer (43,52). Electron microscopy images also showed that the peptidoglycan layer of the ⌬sll1213 strain was less electron dense than in the ⌬sll1951 strain or the Synechocystis wild type (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Secretion and subsequent self-assembly require calcium (35), and it is assumed that the RTX repeat domain (characteristic of type I secreted proteins) that is located adjacent to the C-terminal secretion signal is responsible for at least some of the calcium interaction; whether there is a second domain to complete subunit-subunit interactions is unknown. The S layer is attached to the outer membrane (OM) surface by interaction of an N-terminal attachment domain of approximately 200 amino acids (18) with the fraction of lipopolysaccharide (LPS) that is modified with an O-polysaccharide (3,52).…”
mentioning
confidence: 99%
“…Mutations (8) and truncations (9) in the RsaA extreme N terminus lead to an S-layer shedding phenotype. A species of smooth lipopolysaccharide (SLPS), whose O side chain is composed at least in part of N-acetylperosamine, is found on the outer membrane of C. crescentus (2). This SLPS is at least involved in S-layer anchoring, since strains deficient in O side chain biogenesis shed S-layer (2), (40).…”
mentioning
confidence: 99%